2023
DOI: 10.3390/educsci13030241
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Four Universities on Both Sides of the Taiwan Strait Regarding the Cognitive Differences in the Transition from STEM to STEAM in Design Education

Abstract: There have been many studies on the effectiveness of the STEAM model since its integration into design education, but further investigation is needed to determine whether teachers and students truly understand the meaning of STEAM. The aim of this study is to evaluate people’s perceptions of the STEAM model in design education. Respondents from four universities on both sides of the Taiwan Strait participated in the study. Following expert evaluation and a number of tests, the revised questionnaire was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…In this study, the aim was to assess perceptions of the STEAM model in design education among respondents from four universities on both sides of the Taiwan Strait [4]. The findings demonstrated that respondents' restricted global outlook is attributable to their exposure to local universities.…”
Section: Contribution 11: Comparison Of Four Universities On Both Sid...mentioning
confidence: 97%
“…In this study, the aim was to assess perceptions of the STEAM model in design education among respondents from four universities on both sides of the Taiwan Strait [4]. The findings demonstrated that respondents' restricted global outlook is attributable to their exposure to local universities.…”
Section: Contribution 11: Comparison Of Four Universities On Both Sid...mentioning
confidence: 97%
“…Aunque ha habido avances en la definición de STEAM y en su aplicación a través de estudios empíricos -que podrían proporcionar orientaciones para su utilización en el aula (Bases & García, 2021;EL-Deghaidy et al, 2017;Sun et al, 2023)T-, la evidencia disponible aún es limitada en cuanto a investigaciones que puedan evaluar el nivel de autopercepción en el uso de este enfoque por parte de los docentes de ciencias naturales en la planificación, ejecución y evaluación de sus clases.…”
Section: Introductionunclassified
“…In this context, some studies report that in order to achieve these challenges, it is necessary to start from appropriate teacher training with this approach, a curricular alignment to integrate other disciplines in their subjects, and the consolidation of learning communities for the strengthening of sustainable educational networks [15,16]. On the other hand, there is a solid consensus that the STEAM approach has a relatively low level of standardization and that the theorization criteria are highly diverse, so some studies differ on its vision in terms of inter-, trans-and multidisciplinarity or even the addition and positioning of letters in its acronym [5,[17][18][19], which is also a challenge to overcome. In part, all of this likely creates some teacher barriers, especially in the natural sciences, that limit the implementation of STEAM in their classrooms [13,20,21].…”
Section: Introductionmentioning
confidence: 99%